PSXII-3 Rumen microbiome from beef steers undergoing grain adaptation with steam-flaked corn varying in bulk density - Nardi, Kaue Tonelli (J Anim Sci, 2020)
The effects of steam-flaked corn bulk density during grain adaptation phase on ruminal microbiome were evaluated. Crossbred-Angus ruminally cannulated steers (n = 6; BW = 405 ± 42 kg) were assigned to a randomized complete block design (block = body weight) to 1 of 2 grain adaptation strategies: 1) steam-flaked corn (SFC) bulk density of 335 g/L; and 2) 412 g/L. Steers were ad libitum fed, individually, during 6-7d phases, consisting of: HAY, followed by the STEP-UP1 through STEP-UP4, diets, respectively, in which roughage was gradually replaced with grain until FINISHER diet was fed. Respective SFC bulk densities were fed throughout STEP-UP diets, while the FINISHER diet consisted of 335 g/L strategy only for both groups. Ruminal fluid samples (100 mL) were collected on d-5 of each step, at 6h post-feeding for DNA extraction. Microbiome data were sequenced by Illumnia® NovaSeq™ 6000 (16S rRNA). The SFC bulk density did not affect (P > 0.50) the relative abundance (RA) for any taxonomy classification. Regardless of SFC bulk density, inclusion of grain throughout adaptation phases affected domain (P ≤ 0.03) when initial phases were compared to FINISHER. Phylum RA were affected (P ≤ 0.05) for Actinobacteria (27%), Bacteroidetes (11%), and Euryarchaeota (2%). Within Class RA were affected (P ≤ 0.04) for Clostridia (46%), Actinobacteria (27%), and Bacilli (5%). Order effects on RA were observed (P ≤ 0.04) for Clostridiales (45%), Coriobacteriales (25%), and Lactobacillales (4%). Within Family RA was affected (P ≤ 0.03) for Coriobacteriaceae (25%), Lachnospiraceae (27%), Ruminococcaceae (6%), and Lactobacillaceae (4%), while a tendency (P = 0.09) was observed for Veillonellaceae (1%). In Genus, RA was affected (P ≤ 0.01) for Olsenela (22%), Pediococcus (3%), and Butyrivibrio (3%). As steers advance through subsequent grain adaptation phases until the FINISHER, more meaningful ruminal microbiome changes are observed than SFC density change.